Features of the formation of biochemical mechanisms of energy supply in the process of endurance development female athletes in sports aerobics - Артем’єва, Галина; Хорькова, Марина (Slobozhanskyi Herald of Science and Sport, 2019)
Galyna Artemyeva & Maryna Khorkova The duration of the competitive program in sports aerobics is about 1.5 minutes, during which the athlete must perform high-intensity complex coordination movements that are combined with acrobatic elements. The implementation of these exercises is necessarily subject to musical accompaniment, which sets the pace of exercise. With the athlete advanced training, the competitive program acquires changes and is saturated with more complex elements. In this regard, the trainers are constantly faced with the task of selecting exercises that would be able to solve the problem of developing the optimal level of endurance, which will allow more technically complete the given exercises. Since sports aerobics is a young sport that is gaining its development, today the basis for many years of training athletes has not yet been formed theoretically. The issues of developing endurance also remain uncertain, and it does not allow coaches to more fully build the training process of their pupils. Purpose: to find out the features of the formation of biochemical mechanisms of energy supply in the process of endurance development female athletes in sports aerobics. Materials & Methods: the study was organized on the basis of the municipal out-of-school educational institution "Center for Children and Youth Creativity Dream" of the city of Kryvyi Rig, which was attended by 10 female athletes 14–15 years old, at the stage of basic sports training. In the process of the experiment, the following methods were used: theoretical analysis and generalization of scientific and methodological literature; study of documentary materials, video materials of competitions, pedagogical observation, pedagogical testing, methods of mathematical statistics. Results: presented results of a study of the features of the formation of biochemical mechanisms of energy supply in the process of development of endurance athletes in sports aerobics. Experimental data indicate that in the process of developing endurance of athletes in sports aerobics, the efficiency of the glycolytic mechanism of ATP resistance increased, and a positive effect of the proposed funds on the adaptation processes in the test organism during the transition from creatine-phosphate mechanism of energy supply to glycolytic was revealed. Conclusions: compositions in sports aerobics are marked by the complex coordination nature of the exercises, which must also be performed with great intensity and high pace throughout the competition program. Therefore, the development of such a physical quality as endurance is very important for athletes of this sport. The duration of the competitive program in sports aerobics determines the formation of the leading mechanisms of energy supply in the process of endurance development, namely: the efficiency of the glycolytic mechanism of ATP resistance, as well as adaptation processes in the body of athletes during the transition from creatine phosphate to glycolytic mechanisms, increase.